Living side-by-side? An analysis of the changing relationship between race, space and class in Cape Town, 1980-2011 - Solomon, Jean-Paul (Department of Sociology, 2019)
The aim of this project was to explore the changing relationship between race, space and class in Cape Town during the 1980-2011 period by using the social polarisation vs professionalisation debate as the starting point. The previous working on this debate, as it pertains to Cape Town, took place prior to the availability of the 2011 census data and this project continued that work. Based on the data, the growth of high-income occupations continued, in the preceding decade, combined with considerable growth in middle-income non-manual occupations and an improved educational profile of the employed population. However, this project goes beyond that earlier work, by examining the changing racial composition of the relevant occupational groups in relation to the composition of the working age population at each data point. The spatial or geographical analyses uses both a GIS platform to map the changing distribution of the races, occupational classes and the unemployed, as well as two segregation indices aimed at better understanding the city-wide impacts of those geographical changes. The GIS work uses concepts like suburb and ghetto, both of which are ubiquitous in urban studies literature, as a backdrop, but ultimately asks the following question regarding the spatial changes: What are the spatial implications of a deracialising and professionalising labour market? Ultimately, the findings show that despite the aforementioned deracialisation of high-income and middle-income occupations, Black Africans and Coloured remained most affected by unemployment. Furthermore, in spite of all these changes, Cape Town was still profoundly racially segregated in 2011.